Let and be real numbers with . If is a root of the equation , and is a root of and , then the equation has a root that satisfies:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Solving the quadratic equation that α is a root of, namely, a 2 x 2 + b x + c = 0 , I get:
x = 2 a 2 − b ± b 2 − 4 a 2 c
First note: b 2 − 4 a 2 c ≥ 0 . (Note that the other discriminants should be nonnegative as well. I'm just not considering them at the moment.)
Assume b = 0 .
⇒ − 4 a 2 c ≥ 0 ⇒ c ≤ 0 .
This implies α = 2 a 2 − 4 a 2 c because α > 0 (i.e., we cannot have α = − 2 a 2 − 4 a 2 c ),
and β = 2 a 2 4 a 2 c (because β > 0 as well).
If c = 0 , then α = β = 0 , which contradicts 0 < α < β .
If c < 0 , then β is imaginary, which also contradicts 0 < α < β .
Therefore, b = 0 .
Assume b > 0 .
Case 1: α = 2 a 2 − b − b 2 − 4 a 2 c .
α > 0 leads to:
− b − b 2 − 4 a 2 c > 0
⇔ − b > b 2 − 4 a 2 c ,
which is impossible. So, α = 2 a 2 − b − b 2 − 4 a 2 c .
Case 2: α = 2 a 2 − b + b 2 − 4 a 2 c .
α > 0
⇔ − b > − b 2 − 4 a 2 c
⇔ b 2 < b 2 − 4 a 2 c
⇔ c < 0 .
I conclude that for b > 0 , we must have α = 2 a 2 − b + b 2 − 4 a 2 c and c < 0 .
Still assuming b > 0 , examine the two roots of the equation that β is a root of (namely, a 2 x 2 − b x − c = 0 ):
x = 2 a 2 b ± b 2 + 4 a 2 c .
Assume β = 2 a 2 b + b 2 + 4 a 2 c .
α < β
⇔ − b + b 2 − 4 a 2 c < b + b 2 + 4 a 2 c
⇔ b 2 − 4 a 2 c < 2 b + b 2 + 4 a 2 c
⇔ b 2 − 4 a 2 c < 4 b 2 + b 2 + 4 a 2 c + 4 b b 2 + 4 a 2 c
⇔ − 8 a 2 c − 4 b 2 < 4 b b 2 + 4 a 2 c
⇔ − b 2 − 2 a 2 c < b b 2 + 4 a 2 c
Invoking b 2 + 4 a 2 c ≥ 0 , we find − b 2 − 2 a 2 c ≤ 2 a 2 c < 0 .
That means the inequality α < β is true.
Now, assume β = 2 a 2 b − b 2 + 4 a 2 c
α < β
⇔ − b + b 2 − 4 a 2 c < b − b 2 + 4 a 2 c
⇔ b 2 − 4 a 2 c < 2 b − b 2 + 4 a 2 c
⇔ b 2 − 4 a 2 c < 4 b 2 + b 2 + 4 a 2 c − 4 b b 2 + 4 a 2 c
⇔ − b 2 − 2 a 2 c < − b b 2 + 4 a 2 c
⇔ b 2 + 2 a 2 c > b b 2 + 4 a 2 c
⇔ b 2 + 4 a 2 b 2 c + 4 a 4 c 2 > b 4 + 4 a 2 b 2 c
⇔ a 4 c 2 > 0 ,
which is always true. Therefore, this combination of α and β also works in the case b > 0 .
It is time to compare γ to α and β for the cases A) α = 2 a 2 − b + b 2 − 4 a 2 c and β = 2 a 2 b + b 2 + 4 a 2 c and B) α = 2 a 2 − b + b 2 − 4 a 2 c and β = 2 a 2 b − b 2 + 4 a 2 c .
Case A: α = 2 a 2 − b + b 2 − 4 a 2 c and β = 2 a 2 b + b 2 + 4 a 2 c
We must show that one of the roots of a 2 x 2 + 2 b x + 2 c = 0 is such that α < x = γ < β .
Take γ = 2 a 2 − 2 b + 4 b 2 − 8 a 2 c .
Otherwise, γ = 2 a 2 − 2 b − 4 b 2 − 8 a 2 c < 0 (which contradicts γ > 0 ).
α < γ
⇔ − b + b 2 − 4 a 2 c < − 2 b + 4 b 2 − 8 a 2 c
⇔ b + b 2 − 4 a 2 c < 4 b 2 − 8 a 2 c
⇔ b 2 + b 2 − 4 a 2 c + 2 b b 2 − 4 a 2 c < 4 b 2 − 8 a 2 c
⇔ b b 2 − 4 a 2 c < b 2 − 2 a 2 c
(since c < 0 , I can square both sides)
⇔ b 4 − 4 a 2 b 2 c < b 4 − 4 a 2 b 2 c + 4 a 4 c 2
⇔ 0 < a 4 c 2 ,
which is always true. Therefore, α < γ when b > 0 .
γ < β
⇔ − 2 b + 4 b 2 − 8 a 2 c < b + b 2 + 4 a 2 c
⇔ 4 b 2 − 8 a 2 c < 3 b + b 2 + 4 a 2 c
⇔ 4 b 2 − 8 a 2 c < 9 b 2 + b 2 + 4 a 2 c + 6 b b 2 + 4 a 2 c
⇔ − b 2 − 2 a 2 c < b b 2 + 4 a 2 c
Since − b 2 − 2 a 2 c ≤ 2 a 2 c < 0 (by b 2 + 4 a 2 c ≥ 0 ), − b 2 − 2 a 2 c < b b 2 + 4 a 2 c is true.
Therefore, γ < β .
Case B: α = 2 a 2 − b + b 2 − 4 a 2 c and β = 2 a 2 b − b 2 + 4 a 2 c
α < γ has already been done above.
γ < β
⇔ − 2 b + 4 b 2 − 8 a 2 c < b − b 2 + 4 a 2 c
⇔ 4 b 2 − 8 a 2 c < 3 b − b 2 + 4 a 2 c
(Note that we cannot have 3 b − b 2 + 4 a 2 c ≤ 0 because c < 0 , so we can continue with equivalence)
⇔ 4 b 2 − 8 a 2 c < 9 b 2 + b 2 + 4 a 2 c − 6 b b 2 + 4 a 2 c
⇔ b b 2 + 4 a 2 c < b 2 + 2 a 2 c
⇔ b 4 + 4 a 2 b 2 c < b 4 + 4 a 2 b 2 c + 4 a 4 c 2
⇔ 0 < a 4 c 2 ,
which is a true statement. Therefore, γ < β .
Now, consider b < 0 .
Case 1: α = 2 a 2 − b − b 2 − 4 a 2 c .
α > 0
⇔ − b > b 2 − 4 a 2 c
⇔ b 2 > b 2 − 4 a 2 c
⇔ c > 0 .
Subcase I: β = 2 a 2 b − b 2 + 4 a c .
α < β
⇔ − b + b 2 − 4 a 2 c < b − b 2 + 4 a 2 c
⇔ b 2 − 4 a 2 c < 2 b − b 2 + 4 a 2 c
b 2 − 4 a 2 c < 2 b − b 2 + 4 a 2 c is impossible, so we cannot have this combination of α and β .
Subcase II: β = 2 a 2 b + b 2 + 4 a 2 c .
α < β
⇔ − b − b 2 − 4 a c < b + b 2 + 4 a 2 c
⇔ − b 2 − 4 a 2 c < 2 b + b 2 + 4 a 2 c
Since − 3 b 2 < 4 a 2 c is true (by noting c > 0 ) and is equivalent to 2 b + b 2 + 4 a 2 c > 0 , we can conclude α < β .
Take γ = 2 a 2 − b + 4 b 2 − 8 a 2 c .
α < γ
⇔ − b − b 2 − 4 a 2 c < − 2 b + 4 b 2 − 8 a 2 c
⇔ − b 2 − 4 a 2 c < − b + 4 b 2 − 8 a 2 c ,
which is a true statement (since b < 0 ). That is, α < γ has been shown.
γ < β
⇔ − 2 b + 4 b 2 − 8 a 2 c < b + b 2 + 4 a 2 c
⇔ 4 b 2 − 8 a 2 c < 3 b + b 2 + 4 a 2 c
⇔ 4 b 2 − 8 a 2 c < 9 b 2 + b 2 + 4 a 2 c + 6 b b 2 + 4 a 2 c
⇔ − 6 b 2 − 1 2 a 2 c < 6 b b 2 + 4 a 2 c
⇔ b 2 + 2 a 2 c > − b b 2 + 4 a 2 c
⇔ b 4 + 4 a 2 b 2 c + 4 a 4 c 2 > b 4 + 4 a 2 b 2 c
⇔ a 4 c 2 > 0 ,
which is a true statement. Therefore, γ < β .
Case 2: α = 2 a 2 − b + b 2 − 4 a 2 c .
α > 0
⇔ − b > − b 2 − 4 a 2 c ,
which is true, since b < 0 .
Subcase 1: β = 2 a 2 b − b 2 + 4 a c .
α < β
⇔ − b + b 2 − 4 a c < b − b 2 + 4 a 2 c
⇔ b 2 − 4 a 2 c < 2 b − b 2 + 4 a 2 c ,
which is impossible. Therefore, this pair of α and β do no satisfy α < β (for b < 0 ).
Subcase 2: β = 2 a 2 b + b 2 + 4 a c .
α < β
⇔ − b + b 2 − 4 a 2 c < b + b 2 + 4 a 2 c
⇔ − 2 b + b 2 − 4 a 2 c < b 2 + 4 a 2 c
⇔ 4 b 2 + b 2 − 4 a 2 c − 4 b b 2 − 4 a c 2 < b 2 + 4 a 2 c
⇔ − 4 b b 2 − 4 a 2 c < − 4 b 2 + 8 a 2 c
The inequality, − 4 b b 2 − 4 a 2 c < − 4 b 2 + 8 a 2 c , is impossible because the discriminant of a 2 x 2 + 2 b x + 2 c must be nonnegative.
Therefore, I have shown that in every case, where the given conditions are satisfied, α < γ < β .